Feeding cholesterol blunts the proliferative effect of dietary guar gum - Khattak, Muhammad Muzaffar Ali Khan; Mathers, J.C. (1994)
Raised cell proliferation may be a risk factor for cancer (Preston-Martin et al. 1990). Consumption of soluble non-starch plysaccharides e.g. guar gum (GG) is associated with increased crypt cell proliferation (CCP) in animal models (Pell et al. 1992) but neither the mechanism for this response nor its long-term consequences are certain. The present study investigated the interaction between GG and cholesterol feeding on CCP in rats. Four semi-purified diets containing no GG and no cholesterol (Basal), 10 g cholesterol (Ch), 100 g guar gum (GG) and 100 g guar gum plus 10 g cholesterol (GGCh)/kg diet respectively were fed to twenty male Wistar rats (five ratsldiet) for 21 d). Two hours before killing, each animal was injected intraperitoneally with vincristine sulphate for the measurement of CCP (arrested cellskrypt per 2 h) by the crypt microdissection metaphase arrest technique (Goodlad & Wright, 1982) at 10 (A), 50 (B) and 90 (C)% of the length of the small intestine (SI), in the caecum and at 10 (A) and 90 (B)% of the length of the colon.As expected GG-feeding reduced caecal pH and doubled caecal short-chain fatty acid concentration (data not shown). CCP was highest in the proximal SI and declined to the distal colon. At all intestinal sites CCP was increased by GG. Addition of cholesterol to the basal diet had little effect on CCP but appeared to blunt the proliferative effect of GG. .If raised CCP is a risk factor for colo-rectal cancer (Terpstra et af. 1987) the potential 'protective' effect of dietary cholesterol would bear further study.